Atrial fibrillation: Utility of CHADS2 and CHA2DS2-VASc scores as predictors of readmission, mortality and resource utilization. (15th October 2017) - Lahewala, Sopan; Arora, Shilpkumar; Patel, Prashant; Kumar, Varun; Patel, Nirali; Tripathi, Byomesh; Patel, Nilay; Kallur, Kamala Ramya; Shah, Harshil; Syed, Amer; Gidwani, Umesh; Viles-Gonzalez, Juan F.; et al.
Abstract: Background: CHADS2 and CHA2 DS2 -VASc scores are widely used for thromboembolic risk assessment in Atrial Fibrillation(AF) cohort, however further utilization to predict outcomes is understudied. Method: HCUP's National Readmission Data(NRD) 2013 was queried for AF admissions using ICD-9-CM code 427.31 in principal diagnosis field. Patients with mitral valve disease or repair/or replacement were excluded to estimate population with non-valvular AF only. CHADS2 and CHA2 DS2 -VASc were calculated for each patient. Hierarchical two-level logistic and linear models were used to evaluate study outcomes in terms of mortality, 30 or 90-day readmissions, length of stay(LOS) and cost. Result: Of 116, 450 principal non-valvular AF admissions(50.2% female and 43.1% age ≥ 75 years) 29, 179 patients were readmitted, with total 40, 959 readmissions. Higher CHADS2 and CHA2 DS2 -VASc score were associated with increased mortality from 0.4% for CHADS2 of 0 to 3.2% for score of 6 and from 0.2% for CHA2 DS2 -VASc of 0 to 3.2% for score ≥ 8. LOS increased from 2.20 days for CHADS2 of 0 to 5.08 days for score of 6, while cost increased from $7888 to $11, 151. 30-day readmission rate increased from 8.9% for CHADS2 of 0 to 26.0% for score of 6, and 90-day readmission rate increased from 15.2% to 39%. CHA2 DS2 -VASc scoring similarly demonstrated a trend towards increasing readmission rate, LOS and cost for higher scores. Also, similar results were seen in hierarchical modeling with increment of CHADS2 and CHA2 DS2 -VASc scores. Conclusion: CHADS2 and CHA2 DS2 -VASc scores can be used as quick surrogate markers for predicting outcomes beyond thromboembolic risk. Physician familiarity with these systems makes them easy to use bedside clinical tools to improve outcomes and resource allocation.